Workers, Migrants, and Queers: The political economy of community among illegalised sex workers in Athens - Sampethai, Valentini (Anti-Trafficking Review, 2022)
This article unpacks practices of collaboration and community-building among sex workers in Athens, weaving them with an analysis of labour and illegalisation. In the field, cis and trans, local and migrant workers alike pointed to the pervasive material realities of harm, exploitation, and devaluation as inseparable from the multiple processes of illegalisation and dispossession to which they were subjected. They also demonstrated their own grassroots strategies to deal with these realities. Such practices are examined as concrete efforts of collectivities to survive together through diffuse forms of (state) violence. Nevertheless, the article shows that ‘community’ is by no means straightforward, harmonious, or free from instrumentalism, but situated within a multiplicity of relationships of support, collaboration, subjection, exploitation, obligation, and bondage between sex workers, migrants, and various brokers and gatekeepers. In tracing the connections forged between people occupying multiple positions as informal (sexual) labourers, migrants, and queers, sexuality and gender emerge as inextricable from class, and community as inseparable from political economy.